Techniques Used by Dental Specialists for Extensive Posterior Composite Restorations - Faiqa Shafqat, Waqas Mirza, Maham Liaqat, Umer Mahmood Bajwa, Fahmina Jamil, Darab Fatima Babary, Hira Butt, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the techniques used by dental specialists for placement of extensive posterior composite restorations. Methodology: A cross sectional descriptive was conducted in 150 dentists of College of Dentistry, SMDC, Lahore from June 2019 to July 2020 after obtaining ethical approval from Sharif Medical Research Centre (SMRC). Data was collected using a pre validated questionnaire Results: A statistically non-significant association between the specialty of the dentist the technique used for placement of the composite during restoration (p=0.08). The most commonly used techniques for the placement of posterior composite restorations by dentists of all specialties including Periodontology (88%), Prosthodontics (68.4%), Orthodontics (85.7%), Oral Surgery (91.3%), Oral Pathology (71.4%), Oral Biology (33.3%), Dental materials (75%), Community Dentistry (100%), Operative Dentistry (90.9%) and Oral Medicine (75%) is incremental curing. Practical implication: This study will give an insight on the various techniques used by dentists from various specialties for the placement of composite restorations in posterior teeth. This will in turn help them adopt new and revisit old techniques used by them while placing composite restorations. Conclusion: The most commonly used techniques for the placement of posterior composite restorations by dentists of all specialties is incremental curing followed by use of moisture control during the placement of composites both with and without rubber dam isolation. Keywords: Dental Specialists, Composite Restorations, Posterior Dental Restorations, Incremental Curing